The Influence of Female Workers, Population, and Open Unemployment Rates on Female Labor Force Participation Levels in East Java - Muslinawati, Retno; Aziz, Khalid Fauzi; Trifandha, Siskha (Universitas Gorontalo, 2024)
This research aims to determine the influence of three key factors that influence the level of labor force participation in East Java province, namely the female workforce, population size, and the female open unemployment rate. This research uses secondary data which involves collecting statistical data from official and trusted sources, such as the Central Statistics Agency (BPS) and other related agencies. Data analysis uses statistical methods and descriptive analysis to gain in-depth insight into the relationships between variables. Based on the calculation results, looking at the relationship between variables, it shows that the relationship between female workers and the female open unemployment rate is negative. Meanwhile, the relationship between population size and the female open unemployment rate is positive. According to the t test calculations, it was found that the variables of female labor and population had a positive and significant influence on the labor force participation rate. Meanwhile, the female open unemployment rate has a negative and significant influence on the labor force participation rate. According to the f test, the results show that the three variables have a positive and significant effect on the level of labor force participation.